2022
DOI: 10.1177/2164957x221145940
|View full text |Cite
|
Sign up to set email alerts
|

The Chemo-Gut Study: A Cross-Sectional Survey Exploring Physical, Mental, and Gastrointestinal Health Outcomes in Cancer Survivors

Abstract: Background Cancer treatments, such as chemotherapy, may adversely affect gastrointestinal (GI), physical and mental health in survivors of cancer. Objective This study investigated associations between GI, mental and physical health outcomes, and cancer treatment-related variables, such as chemotherapy, in adult cancer survivors. Methods A one-time cross-sectional survey with patient-reported outcomes was used. Cancer survivors (N = 317) aged ≥18 years, living in Canada, who completed cancer treatments were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Moreover, compared to healthy peers with no history of cancer, the relative abundances of specific taxa remained different in survivors up to 5-years post-treatment; Certain bacterial taxa were correlated with psychosocial outcomes, including increased depression and poorer cognitive function [28]. Our previous work also found that survivors experience chronic, moderate to severe, GI symptoms, lasting for an average of 2.5 years post-treatment, and that higher GI symptom burden is associated with poorer mental health [29]. However, the potential impact of diet and exercise behaviours on survivors' gut microbiota remains to be elucidated.…”
Section: Diet Exercise and Cancermentioning
confidence: 78%
See 4 more Smart Citations
“…Moreover, compared to healthy peers with no history of cancer, the relative abundances of specific taxa remained different in survivors up to 5-years post-treatment; Certain bacterial taxa were correlated with psychosocial outcomes, including increased depression and poorer cognitive function [28]. Our previous work also found that survivors experience chronic, moderate to severe, GI symptoms, lasting for an average of 2.5 years post-treatment, and that higher GI symptom burden is associated with poorer mental health [29]. However, the potential impact of diet and exercise behaviours on survivors' gut microbiota remains to be elucidated.…”
Section: Diet Exercise and Cancermentioning
confidence: 78%
“…Participants for this secondary analysis were combined from both the Chemo-Gut Pilot study [28] and the Chemo-Gut Survey study [29]. The demographic, clinical, and GI outcome related data were similar between the two studies, thus allowing us to pool the results for the health behaviour and GI outcome data.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations